Religion and law in the Western Sephardi community: some remarks from the case of Livorno during the Early Modern Period - Dimant, Mauricio (Vergentis, 2017)
This article examines documents of the Sephardic Community of Livorno during the 17th century, with special attention to the escamot that refer to legal aspects of Jewish life in this port-city, in order to contribute to the study of the religious community experiences during political changes in Europe in the Early Modern Period. This enables analysis of how, and to what extent, the mechanisms of communal socialization and social control in the public and private spheres were related to the process in which the territorial authority and the political control of its borders were reinforced in Tuscany. It argues that Sephardic community legal decisions reinforced political processes in Livorno (and Tuscany), rather than merely been unconnected to them. This argument implies reconsidering not only the role of Diasporic religious communities in local political context, but also the role of local context in the tension between religion and law. From this perspective, it is possible to deepen our understanding of the experience of religious communities regarding the conception on Justice.